(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This study is dedicated to the phenomenon of Tuvan throat singing, known as khoomei, with a focus on the analysis of professionalism in the context of oral tradition in the works of Tuvan folk khoomei performers. It examines the theory of professionalism in oral tradition and the presence of specific criteria of this theory through the analysis of performance techniques and the characteristics of the styles of such folk khoomei artists as Kaigal-ool Khovalyg, Aldyn-ool Sevek, Gennady Tumat, Andrey Opey and Andrey Сhuldum-ool. The role of these performers in preserving and transmitting this unique art form is emphasized, along with an analysis of their compositional structure, repertoire, and individual style. Through a comprehensive analysis, the study highlights how professionalism influences the sustainability and evolution of Tuvan khoomei in contemporary society.